EFFECTIVE HUMAN RESOURCE MANAGEMENT STRATEGY: IMPROVING EXCELLENT SERVICE FOR COMPETITIVE ADVANTAGE - Lailatul Fitriyah; Sholihah, Imroatus (Universitas Nurul Jadid, 2023)
This research aims to determine the role of human resource management in improving excellent service at TPA Arrahmah Probolinggo. This type of research uses descriptive qualitative analysis research. Case study at TPA Arrahmah Problinggo using data collection techniques through observation, interviews and documentation. The research results show that improving excellent service through human resource management at TPA Arrahmah includes, firstly, human resource planning carried out by the Islamic boarding school education bureau by analyzing report data from the school principal. Second, recruitment of human resources is carried out using steps including determining the requirements for teaching staff and determining sources and recruitment methods. Third, human resource selection includes receiving application letters, selection interviews, and application decisions. Fourth, the training and development of human resources include child handling training, which includes knowledge of child psychology and BimTech for preparing PTK and encouraging those completing their studies. Fifth, human resource assessments are carried out informally regarding personal achievements at work. Informal assessments are continuously carried out by the principal regarding the performance of his subordinates objectively, which includes skills, discipline, behaviour, work results and levels of absenteeism.